2004
DOI: 10.1352/0047-6765(2004)42<338:cqolat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Based Quality of Life Assessment: The Maryland Ask Me! Project

Abstract: The concept of quality of life currently impacts program development, service delivery, management strategies, and outcome evaluation in the area of intellectual disabilities. Maryland uses peer interviewers to assess consumer-perceived quality of life among adult recipients of MR/DD services and supports. In this article we describe the survey instrument and procedures and discuss assessment issues of quality of responses, acquiescence, and proxy respondents. We present the psychometric properties for eight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
85
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 9 publications
2
85
1
1
Order By: Relevance
“…This finding is consistent with previous studies that reported a better QOL in younger group, with other populations (Lucas-Carrasco et al, 2011;Trompenaars et al, 2005). Bonham et al (2004) observed that younger people with ID reported higher scores of personal development and interpersonal relations.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding is consistent with previous studies that reported a better QOL in younger group, with other populations (Lucas-Carrasco et al, 2011;Trompenaars et al, 2005). Bonham et al (2004) observed that younger people with ID reported higher scores of personal development and interpersonal relations.…”
Section: Discussionsupporting
confidence: 92%
“…Scores were significantly higher (better QOL) in participants with mild ID, compared to the group of people with moderate ID. Higher levels of self-determination, rights, and material well-being were reported in people with higher intellectual or communication/speaking skills (Bonham et al, 2004). This is confirmed by Gardner and Carran (2005) that found better QOL in people with mild/moderate ID than participants with other levels of ID.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations